1, 3‐Benzodioxole Tagged Lidocaine Based Ionic Liquids as Anticancer Drug: Synthesis, Characterization and In Silico Study. Issue 9 (28th February 2023) - Sangeeta,; Sonaxi,; Tomar, Ravi; Agrawal, Swati; Sarkar, Anjana
Abstract: Skin cancer is by far the most frequent type of cancer in humans which gradually increases day by day. Numerous treatments are traditionally and conventionally available in the market but due to various factors such as high dose, high cost, adverse side effects, and so on. So, these treatments require novel routes of action and target drugs that can overcome these drawbacks. As per the ritual of our research group to design a new drug for mankind, we have synthesized derivatives of 1, 3‐Benzodioxole tagged lidocaine‐based ionic liquid in the present work and characterized using techniques like 1 H, 13 C NMR, and infrared spectroscopy. The in‐silico studies were conducted which provided information regarding the binding mode of active 1, 3‐benzodioxole‐derived ILs with the tubulin protein (1TUB) receptor. The binding affinity for [Pip‐Lid]OAc and [Pip‐Lid]OTf are −384.47 kJ/mol and −355.74 kJ/mol respectively. The properties of these ionic liquids like ADMET, blood‐brain barrier permeability, and drug‐likeliness proved the potency of the given compound for the treatment of skin cancer. Briefly, the current study showed the good anticancer potential of synthesized ionic liquids against skin cancer. Abstract : Skin cancer is by far the most frequent type of cancer in humans which gradually increases day by day. In the present work, we have synthesized and characterized derivatives of 1, 3‐Benzodioxole tagged lidocaine‐based ionic liquid using 1 H, 13 C NMR, and infrared spectroscopy. Also, the in‐silico studies were conducted which provided information regarding the binding mode of active 1, 3‐benzodioxole‐derived ILs with the tubulin protein (1TUB) receptor. Briefly, the current study showed the good anticancer potential of synthesized ionic liquids against skin cancer.